2021
DOI: 10.1093/biosci/biab065
|View full text |Cite
|
Sign up to set email alerts
|

Design Criteria for Process-Based Restoration of Fluvial Systems

Abstract: Process-based restoration of fluvial systems removes human constraints on nature to promote ecological recovery. By freeing natural processes, a resilient ecosystem may be restored with minimal corrective intervention. However, there is a lack of meaningful design criteria to allow designers to evaluate whether a project is likely to achieve process-based restoration objectives. We describe four design criteria to evaluate a project's potential: the expansion of fluvial process space and connectivity lost beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 49 publications
0
31
0
1
Order By: Relevance
“…Our results contrast, however, with results reported from some western North American studies, where decreased maximum summer stream temperatures have been observed below beaver ponds (Dittbrenner, 2019; Weber et al, 2017, but see Jones et al, 2018). The divergent findings from these studies likely point to a host of context‐specific or contingent outcomes that may be expected from beaver‐constructed ponds on streams (Ciotti et al, 2021; Nash et al, 2021; Pilliod et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results contrast, however, with results reported from some western North American studies, where decreased maximum summer stream temperatures have been observed below beaver ponds (Dittbrenner, 2019; Weber et al, 2017, but see Jones et al, 2018). The divergent findings from these studies likely point to a host of context‐specific or contingent outcomes that may be expected from beaver‐constructed ponds on streams (Ciotti et al, 2021; Nash et al, 2021; Pilliod et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…North American beaver (Castor canadensis) are considered ecosystem engineers because they can fundamentally transform stream and riparian ecosystems through a number of their activities, most notably, creating ponds by building dams and impounding water (Jones et al, 1996;Larsen et al, 2021;Wright et al, 2002). These attributes have inspired much interest in the potential for beaver to play a role in process-based stream restoration (Ciotti et al, 2021;Johnson et al, 2020;Pollock et al, 2015). This approach is often termed 'beaverrelated restoration' or BRR.…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, and for far too long, river restoration and rehabilitation has been carried out at the reach-scale and in an ad-hoc manner, treating reaches in isolation, and independent of their position in catchment [ 66 , 67 ]. A shift to a more systemic approach to management of fluvial corridors and river systems, incorporates both local and catchment scale (or larger scale, region, State or National) rehabilitation decision-making, and is situated in the context of nature-based and process-based solutions [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Geomorphic heterogeneity metrics pair well with descriptors of process space, utilization of process space, and geomorphic trajectory. Confinement, or process space (sensu Ciotti et al, 2021) describes the proportion of the valley bottom the river can actively reshape (e.g., a ratio of non-terrace to total valley bottom area). Process space utilization is the degree to which the river is actively reshaping the space available to it (e.g., the proportion of the channel and floodplain area occupied by channels either at a given time or cumulatively over a period of time).…”
Section: Contextualizing Geomorphic Heterogeneitymentioning
confidence: 99%